Active noise control of construction noise - Lee, Yen Theng (Nanyang Technological University, 2024)
Urban noise pollution is a ubiquitous but often neglected threat to public health. Particularly, the low-frequency noises emitted by construction equipment and machines are of concern due to the chronic health issues that can develop from long term exposure. Current adopted noise control methods are dominated by passive measures, which are easily scalable, but have limited effectiveness for the deleterious low-frequency range. Active Noise Control (ANC) methods have been demonstrated the ability to mitigate these low frequencies appreciably, but have yet to achieve compelling cost-effectiveness for widespread adoption. Hence, a low-cost ANC solution is explored with the STM32 H723ZG board. Several ANC algorithms (MISO Feedforward, SISO Feedback, MIMO Feedforward) have been developed to explore the board capabilities to effectively control power generator noise. Simulated testing in the laboratory and field experiments have shown the success of the low-cost implementation, with substantial noise reduction of >10dBC at far-field locations of >200cm from the noise source.